2013
DOI: 10.1128/jcm.00682-13
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of the Vitek MS Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry System for Identification of Gram-Positive Aerobic Bacteria

Abstract: g Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF) is gaining momentum as a tool for bacterial identification in the clinical microbiology laboratory. Compared with conventional methods, this technology can more readily and conveniently identify a wide range of organisms. Here, we report the findings from a multicenter study to evaluate the Vitek MS v2.0 system (bioMérieux, Inc.) for the identification of aerobic Gram-positive bacteria. A total of 1,146 unique isolates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(67 citation statements)
references
References 42 publications
2
64
0
1
Order By: Relevance
“…Few laboratories routinely include anaerobic media or culture conditions as part of the workup for CSF specimens in light of the fact that anaerobes are not the organisms classically associated with acute bacterial meningitis. Our patient's P. acnes isolate was initially cultured anaerobically on brucella blood agar, and its identification was later confirmed using two matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) platforms, the Bruker Biotyper (software version 3.0; Bruker Daltonics, Billerica, MA) and Vitek MS (database version 2.0; bioMérieux) (23,24). Although details of culture methods are not described in all previous case reports, broth me- dium, such as thioglycolate or Robertson's chopped meat broth, and cysteine Trypticase semisolid agar were used to isolate P. acnes from CSF specimens (25).…”
Section: Case Reportmentioning
confidence: 99%
“…Few laboratories routinely include anaerobic media or culture conditions as part of the workup for CSF specimens in light of the fact that anaerobes are not the organisms classically associated with acute bacterial meningitis. Our patient's P. acnes isolate was initially cultured anaerobically on brucella blood agar, and its identification was later confirmed using two matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) platforms, the Bruker Biotyper (software version 3.0; Bruker Daltonics, Billerica, MA) and Vitek MS (database version 2.0; bioMérieux) (23,24). Although details of culture methods are not described in all previous case reports, broth me- dium, such as thioglycolate or Robertson's chopped meat broth, and cysteine Trypticase semisolid agar were used to isolate P. acnes from CSF specimens (25).…”
Section: Case Reportmentioning
confidence: 99%
“…The VITEK MS identification system is based on comparison of the characteristics of the obtained spectra with those of the VITEK MS v2.0 database (7,8). All of the statistical analyses were performed with SPSS 19.0.…”
Section: Discussionmentioning
confidence: 99%
“…The system reported the best identification with confidence values from 0 to 99.9%. Escherichia coli ATCC 8739 was used as internal identification control during the whole analysis process (7,8).…”
Section: Maldi-tof Mass Spectrometrymentioning
confidence: 99%
“…Branda et al evaluated the VITEK MS system for identification of 226 isolates of fastidious gram-negative bacteria; 97% and 96% of the fastidious gram-negative bacteria studied were accurately identified to the genus and species levels, respectively (22 ). Rychert et al evaluated the Vitek MS system for identification of 1146 aerobic gram-positive bacteria and showed that 93% were correctly identified to the species level, with an additional 3% identified only to the genus level because of a split identification with multiple matching species within the same genus (including Listeria monocytogenes with matches to L. monocytogenes, Listeria ivanovii, and Listeria welshimeri) (23 ). Karpanoja et al compared the MALDI Biotyper and VITEK MS IVD systems for identification of viridans group streptococci using 54 type strains and 97 blood culture isolates (24 ).…”
Section: Performance Of Maldi-tof Ms For Identification Of Aerobic Bamentioning
confidence: 99%